On the Effect of Central Jet in Solid Cone Pressure-Swirl Atomizers / Ahmad H. A. Hamid ...[et al.] - A. Hamid, Ahmad H.; Kasolang,, Salmiah; A. Ghaffar,, Zulkifli; M. Noh, Mohd H. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Studies on swirl spray have received considerable attention due to its importance in numerous applications. The present study investigates the characteristics of sprays emanating from solid cone pressure swirl atomizers. Several atomizers with different exit orifice diameter were investigated using water at room temperature as the working fluid. The investigation reveals that the jet emanates from the central port significantly modifies the resulting sprays, particularly for atomizers with smaller exit orifice diameter. It is also found that a reduction in exit orifice diameter results in a significant increase in discharge coefficient and an almost linear increase in air core diameter. A semi-empirical correlation is also proposed to predict the axial velocity in terms of the main atomizer dimensions.